Probing a Device's Active Atoms. Issue 19 (13th March 2017) - Studniarek, Michał; Halisdemir, Ufuk; Schleicher, Filip; Taudul, Beata; Urbain, Etienne; Boukari, Samy; Hervé, Marie; Lambert, Charles‐Henri; Hamadeh, Abbass; Petit‐Watelot, Sebastien; Zill, Olivia; Lacour, Daniel; et al.
Abstract : Materials science and device studies have, when implemented jointly as "operando" studies, better revealed the causal link between the properties of the device's materials and its operation, with applications ranging from gas sensing to information and energy technologies. Here, as a further step that maximizes this causal link, the paper focuses on the electronic properties of those atoms that drive a device's operation by using it to read out the materials property. It is demonstrated how this method can reveal insight into the operation of a macroscale, industrial‐grade microelectronic device on the atomic level. A magnetic tunnel junction's (MTJ's) current, which involves charge transport across different atomic species and interfaces, is measured while these atoms absorb soft X‐rays with synchrotron‐grade brilliance. X‐ray absorption is found to affect magnetotransport when the photon energy and linear polarization are tuned to excite FeO bonds parallel to the MTJ's interfaces. This explicit link between the device's spintronic performance and these FeO bonds, although predicted, challenges conventional wisdom on their detrimental spintronic impact. The technique opens interdisciplinary possibilities to directly probe the role of different atomic species on device operation, and shall considerably simplify the materials science iterations within device research. Abstract : A new operando technique focuses the materials' characterization onto the device's active atoms by probing it within the device's current. Performing synchrotron‐grade X‐ray absorption spectroscopy onto operating magnetic tunnel junctions reveals that FeO bonds parallel to the device's interface are compatible with high spintronic performance. This maximized causality between materials and device science portends a paradigm shift in device research philosophy.